The Role of Generation Z on Social Media in Facilitating Political Activism in the Digital Era - Diah Nafa Rani Nabila; Trisakti Handayani; Budiono (Yayasan Ilomata, 2026)
This study aims to examine the role of Generation Z in utilizing social media as a platform for political activism and mobilization in the digital era, with a particular focus on East Java Province. Social media has evolved into a digital public sphere that enables young people to access political information, express their views, and build political engagement in a more open and dynamic manner. This study employs a descriptive qualitative approach using a case study method involving individual digital activists and the student organization BEM SI East Java Region as research subjects. Data were collected through in-depth interviews, documentation of social media activities, and literature review. The findings indicate that social media plays a significant role in shaping Generation Z’s political communication strategies and encouraging the gradual mobilization of political participation through digital networks. However, digital political activism also faces several challenges, including the spread of disinformation, opinion polarization, social pressure, and concerns regarding digital regulation. This study concludes that social media serves as a strategic instrument in transforming Generation Z’s political participation toward more participatory digital democratic practices, while still requiring strengthened digital literacy and supportive policies to ensure a healthy and inclusive digital space.